2023
DOI: 10.1186/s12913-023-09273-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between changes in the public health nurses’ workforce and the empirical Bayes estimates of standardized mortality ratio: a longitudinal ecological study of municipalities in Japan

Abstract: Background The role of public health nurses (PHNs) in the community is expected to become increasingly important, along with the promotion of a comprehensive community care system. However, a comprehensive study of all municipalities is yet to be undertaken, and the relationship between the workforce of PHNs and health indicators is yet to be clarified. This study examined the effect of workforce change among PHNs, one of the structural indicators of PHNs’ activities regarding changes in the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In Brazil, between February 2019 and September 2020, free training and lifelong learning strategies were offered to health professionals aimed at reducing syphilis, with about 22,000 students participating [ 39 ]. A previous study has already shown that the increase in the number of nurses was significantly associated with chronic diseases [ 40 ]. In this way, it may be able to minimize the vulnerability of access to health services, as observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, between February 2019 and September 2020, free training and lifelong learning strategies were offered to health professionals aimed at reducing syphilis, with about 22,000 students participating [ 39 ]. A previous study has already shown that the increase in the number of nurses was significantly associated with chronic diseases [ 40 ]. In this way, it may be able to minimize the vulnerability of access to health services, as observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The uneven distribution of healthcare resources is a long-standing challenge in China. It is also prevalent in other countries (regions), such as the United States ( 9 ), Portugal ( 10 ), Japan ( 11 ), Kenya ( 12 ), and Southeast Asia ( 13 ). As the largest developing country with a vast land area and a large population, China faces the challenge of maximizing the provision of comprehensive health care services given the constraints on available healthcare resources ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study used a large sample size, namely the number of TB cases in Indonesia, so accurate and significant SMR values could be produced. Next, a study used SMR to examine the relationship between healthcare resources and mortality in 3,360 Japanese cities [17]. However, this study used a smaller sample size, namely the number of TB cases in each district/city in Aceh Province, so the estimated relative risk based on the SMR method was less reliable and allowed overdispersion.…”
Section: Introductionmentioning
confidence: 99%